The "Nation's Conscience:" Assessing Bioethics Commissions as Public Forums - Dzur, Albert W (Kennedy Institute of Ethics journal, 2004)
, As the fifth national bioethics commission has concluded its work and a sixth is currently underway, it is time to step back and consider appropriate measures of success. This paper argues that standard measures of commissions' influence fail to fully assess their role as public forums. From the perspective of democratic theory, a critical dimension of this role is public engagement: the ability of a commission to address the concerns of the general public, to learn how average citizens resolve moral issues in healthcare, and to monitor public opinion on the topics addressed in the commission. Such a public forum role is supported by the critical literature within bioethics, which has deemed some commissions successful, supported more generally by the history of bioethics as a reform discourse that has brought socially important values into the medical domain, and supported more generally still by the example of the great social issues commissions of the 1960s.